Citric acid-assisted combustion-nitridation-denitridation synthesis of well-distributed W-Cu nanocomposite powders. (January 2018) - Chu, Aimin; Wang, Zhiqian; Rafi-ud-din; Dong, Yinghu; Guo, Chenguang; Liu, Wenhui; Xu, Hongmei; Wang, Long
Abstract: A novel method of citric acid-assisted combustion-nitridation-denitridation was developed to prepare the W-Cu composite powders. The preparation process consisted of citric acid-assisted combustion, calcination, nitridation, and denitridation reactions. It was found that the performance of W-Cu composite powders was mainly dependant upon the concentration of initial material i.e. citric acid used. Therefore, the effects of citric acid on the size and morphology of various intermediate products and the final synthesized W-Cu nanocomposite powders were studied in detail. The results indicated that the calcined product synthesized from citric acid (0.02 mol) was comprised of favaginous mass particles with high specific surface area (24 m 2 /g). It was observed that nitridation and denitridation reactions for sample with citric acid (0.02 mol) completed in 1 h at 700 °C and 800 °C, respectively. One the contrary, nitridation and denitridation reactions for the combustion products, synthesized without the use of citric acid, were incomplete under the similar conditions. The W-Cu nanocomposite powders from citric acid (0.02 mol) exhibited the well-distributed spherical particles of 30–50 nm. Citric acid was found to accelerate the reactivity of combustion products to induce a morphology with homogeneous and well-distributed W-Cu nanoparticles. The relative density and hardness of sintered W-Cu composites, prepared from 0.02 mol citric acid, were measured to be 98.8% and 275 HV, respectively. Highlights: A combustion product is prepared by the citric acid assisted LCS method. A novel method of citric acid-assisted LCS-nitridation-denitridation was developed. The citric acid content in solution governs the morphology of various products. W-Cu composites from 0.02 mol citric acid exhibit particles of 30–50 nm.